Reconstructing the Regulatory Framework for Crypto Asset Trading Based on Green Constitutional Principles to Ensure Green Economic Stability - Citra Ayu Deswina Maharani (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, the regulation of crypto asset trading should advance digital economic innovation while simultaneously safeguarding environmental sustainability and long-term green economic stability. In practice, however, Indonesia’s regulatory framework remains largely oriented toward transactional legality and short-term market stability, with limited incorporation of green constitution principles as constitutional and normative foundations. This regulatory gap becomes increasingly problematic given the energy-intensive characteristics of blockchain-based activities and their potential environmental externalities. This study aims to reconstruct the governance of crypto asset trading through the integration of green constitutional principles to ensure sustainable green economic stability. Employing a qualitative library research design with normative legal analysis, this study applies statutory, conceptual, and philosophical approaches. The findings demonstrate that an effective regulatory reconstruction requires the institutionalization of sustainable development, ecological justice, and constitutional accountability as core governance principles. Such an approach positions crypto asset trading not merely as a technological or financial innovation, but as an integral component of a constitutional economic order that harmonizes digital transformation with environmental protection and long-term economic resilience.